Release of synthetic microplastic plastic fibres from domestic washing machines: Effects of fabric type and washing conditions. Issue 1 (15th November 2016) - Napper, Imogen E.; Thompson, Richard C.
Abstract: Washing clothes made from synthetic materials has been identified as a potentially important source of microscopic fibres to the environment. This study examined the release of fibres from polyester, polyester-cotton blend and acrylic fabrics. These fabrics were laundered under various conditions of temperature, detergent and conditioner. Fibres from waste effluent were examined and the mass, abundance and fibre size compared between treatments. Average fibre size ranged between 11.9 and 17.7 μm in diameter, and 5.0 and 7.8 mm in length. Polyester-cotton fabric consistently shed significantly fewer fibres than either polyester or acrylic. However, fibre release varied according to wash treatment with various complex interactions. We estimate over 700, 000 fibres could be released from an average 6 kg wash load of acrylic fabric. As fibres have been reported in effluent from sewage treatment plants, our data indicates fibres released by washing of clothing could be an important source of microplastics to aquatic habitats. Highlights: Washing clothes made from synthetic materials is a potentially important source of microplastic into the environment. This study examined the release of fibres from common fabrics; polyester, polyester-cotton blend and acrylic. Fibre release varied according to wash treatment with various complex interactions. For an average wash load of 6 kg, over 700, 000 fibres could be released per wash.